"Juggling many balls": Working and studying among first‐year nursing students. Issue 21 (1st August 2019) - Christiansen, Angela; Salamonson, Yenna; Crawford, Ruth; McGrath, Belinda; Roach, David; Wall, Peter; Kelly, Mandy; Ramjan, Lucie M.
Abstract: Aims and objectives: To explore the experiences of first‐year nursing students, their motivations for working and how they juggled study and other commitments while engaging in paid work. Background: There has been a global rise in the number of students balancing full‐time study, paid work and other commitments, with the main antecedent financial reasons. Design: Qualitative exploratory study. Methods: Drawn from a larger Australasian sequential exploratory mixed‐method study, this qualitative study was conducted with fifty first‐year undergraduate nursing and midwifery students who commenced their nursing studies in 2017. Telephone or face‐to‐face interviews were conducted with purposively selected students engaged in either nursing or non‐nursing fields of work. Interviews were conducted from April–July 2017. Interviews lasted from 15–40 min. Results were thematically analysed. EQUATOR guidelines for qualitative research (COREQ) applied. Findings: Two main themes and accompanying subthemes were identified. The first theme explored students' motivation behind combining work and study and identified the need for financial security and "me time". The second theme "Juggling many balls" provided insights into the benefits students perceived, how they kept the "balls" in the air and at times dropped "balls" while balancing work, study and other commitments. Conclusions: The motivation behind paid work was mainly financial; however, students also reported work allowed an escape and time for self which had social and health benefits. Working provided a range of positive benefits, including a sense of achievement, improved self‐esteem and financial independence. Relevance to clinical practice: Being able to juggle and multi‐task improved skills such as organisation and the ability to prioritise, all skills that have applicability for the role as registered nurse.